Penyuluhan Bahaya dan Upaya Mitigasi Bencana Hidrometeorologi di Desa Lembah Sari, Kecamatan Batu Layar, Kabupaten Lombok Barat - Muhammad Khalis Ilmi; Hidayat, Ari Ramadhan; Titik Wahyuningsih; Agustini Ernawati; Swahip; Ahmad Zarkasi; Aulia Muttaqin; Erni Yustissiani; Hady Rasikun; Ringgi Puteri Samengasbumi; Feri Irawan; Viara Amaelisa; Febrian Ekasapta Haryadi (Rengganis Jurnal Pengabdian Masyarakat, 2023)
Hydrometeorological disasters are disasters caused by damage to the system in the hydrological cycle, thereby affecting the stability of climate conditions and water reserves on the earth's surface. Hydrometeorological disasters include droughts, floods, storms, forest fires, landslides, cyclones, cold waves and heat waves. On December 6 2021 several areas in West Lombok Regency were affected by flooding caused by extreme weather. One of the areas affected is Lembah Sari Village, Batu Layar District, West Lombok Regency. From the geographical conditions of Lembah Sari Village, it has a high potential for hydrometeological disasters. For this reason, the Community Service Team for the Civil Engineering Study Program (Prodi) at Muhammadiyah University of Mataram carried out outreach related to hydrometeorological disaster mitigation in Lembah Sari Village, Batu Layar District, West Lombok Regency. The method used is counseling with material presentation sessions and question and answer discussions. The activity will be held on August 28 2023. The extension activity can run well and smoothly as seen from the enthusiasm of the people in listening to the presentation of the material which is then followed by a question and answer session.